Car of the future : [videorecording (DVD)] : engineering for the environment - Magliozzi, Tom; Magliozzi, Ray; Lithgow, John, 1945- (WGBH Boston Video, 2008)
With soaring prices at the pump and worries about the global greenhouse, it's no laughing matter. But the car guys turn an expert, comic eye on the promise and pitfalls of tomorrow's auto tech.